Preserving the Integrity of the PPP Model in Victoria, Australia, during the Global Financial Crisis - Foster, Richard (World Bank, Washington, DC, 2015)
The state of Victoria, Australia, under the Partnerships Victoria policy, uses public private partnerships (PPPs) as an important mechanism for meeting public service delivery needs in many social and economic infrastructure sectors. Since 2000, 21 PPPs have reached financial close, representing some $A10.5 billion of investment, about10 percent of Victoria’s total public investment program. Typically, the private sector designs, builds, finances, and maintains or operates the infrastructure and receives revenue consisting of service payments made by the government that are linked to the project company’s performance and the availability of the infrastructure. As in many markets, in Australia the global financial crisis substantially affected the cost and availability of financing for PPPs. Monoline guarantors, who had played a key role in many projects, were early casualties of the crisis, and their exit required new projects to raise debt from banks. Although the Australian banking sector was not affected by the crisis as substantially as in some countries, short-term funding costs and financing availability were significantly altered by a dramatic fall in liquidity. As the crisis unfolded, Victoria sought to maintain the integrity of its well-developed PPP model while meeting the changing situation in the financial markets. This approach required limited and carefully considered changes in the way a small number of finance-related risks were allocated and managed in PPP projects.